2008
DOI: 10.1001/archgenpsychiatry.2007.19
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Error Processing Dysfunctions in Major Depressive Disorder

Abstract: Unmedicated patients with MDD showed reduced accuracy and potentiated error-related negativity immediately after committing errors, highlighting dysfunctions in the automatic detection of unfavorable performance outcomes. New analytic procedures allowed us to show that abnormal reaction to committing errors was accompanied by hyperactivation in rostral ACC and medial PFC regions 80 milliseconds after committing errors and a failure to recruit dorsolateral PFC-based cognitive control. Future studies are warrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
231
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(273 citation statements)
references
References 78 publications
34
231
4
Order By: Relevance
“…Major depression is another condition that can affect the size of the ERN (Ruchsow et al, 2006;Chiu and Deldin, 2007;Holmes and Pizzagalli, 2008), although not always (Schrijvers et al, 2009;Bailey et al, 2015). We saw no relationship between ERN amplitude and the severity of depression symptoms reported on the BDI.…”
Section: Error-related Negativity and Depressionmentioning
confidence: 49%
See 1 more Smart Citation
“…Major depression is another condition that can affect the size of the ERN (Ruchsow et al, 2006;Chiu and Deldin, 2007;Holmes and Pizzagalli, 2008), although not always (Schrijvers et al, 2009;Bailey et al, 2015). We saw no relationship between ERN amplitude and the severity of depression symptoms reported on the BDI.…”
Section: Error-related Negativity and Depressionmentioning
confidence: 49%
“…Individuals with schizophrenia show reductions in the ERN (Alain et al, 2002;Mathalon et al, 2002), whereas those with generalized anxiety disorder (GAD) and OCD show increases (Gehring et al, 2000;Endrass and Ullsperger, 2014;Xiao et al, 2011). The findings in major depressive disorder are mixed, with some studies showing increases in ERN amplitude (Chiu and Deldin, 2007;Holmes and Pizzagalli, 2008;Aarts et al, 2013) and others decreases (Ruchsow et al, 2006) or no difference (Compton et al, 2008;Schrijvers et al, 2009). Co-morbid conditions that occur with depression may account for some of the mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in event-related potentials (ERP) study, it was observed (Holmes and Pizzagalli, 2008) that MDD was associated with a pronounced error negativity effect (ACC signaling) but impaired connectivity between ACC and DLPFC, and abnormal posterior ERP amplitude (Zhu et al, 2010), causing reduced attentional control. Despite of these encouraging findings, neuropsychological studies on inhibition have typically used -7 -the emotional Stroop task, which does not allow distinguishing between active selection of task relevant material and active inhibition of task-irrelevant (emotional) material (Hasher and Zacks, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Because the hypersensitivity to negative events and the tendency to worry about negative outcomes are hallmarks of several affective personality traits or disorders like anxiety and depression (Maner & Schmidt, 2006;Mineka et al, 2003;Wray & Stone, 2005), one may assume that performance monitoring may vary with these affective personality traits. Consistent with this hypothesis, several studies have reported an effect of anxiety or depression on the ERN (e.g., Aarts & Pourtois;2010;Holmes & Pizzagalli, 2008;Olvet & Hajcak, 2008). By contrast, the evidence supporting a systematic modulation of the FRN (and hence the processing of external evaluative feedback) as a function of negative affect is mixed.…”
mentioning
confidence: 96%